“He Who Sings, Prays Twice”? Singing in Roman Catholic Mass Leads to Spiritual and Social Experiences That Are Predicted by Religious and Musical Attitudes - Wald-Fuhrmann, Melanie; Boenneke, Sven; Vroegh, Thijs; Dannecker, Klaus Peter (Frontiers in Psychology, 2020)
Song is an essential element in every religion. In the liturgy of the Roman Catholic Church, theologians expect congregational singing to have several clear-cut effects which can be translated into psychological hypotheses. This study is the first to approach these quantitatively. N = 1603 Catholics from German-speaking countries answered an exhaustive questionnaire that asked whether and to what degree these putative effects were actually experienced by churchgoers. We found that people do, to a large degree, associate feelings of community and spiritual experiences with congregational singing. We also identified relevant intraindividual factors that contribute to the frequency of these experiences, most importantly, religious and musical attitudes. These results are discussed in the light of psychological literature on the effects of group singing on social bonding and wellbeing, but also in the context of theological, ethnomusicological, and sociological research on singing, songs, and spiritual and social experiences.